Análisis del discurso de los medios de comunicación impresos de Riobamba, sobre la campaña de arborización, en el periodo julio-diciembre 2022 - Ponce Alcivar, Jessica Shirley (2024)
ABSTRACT: This research thesis focuses on the analysis of media coverage of the tree planting campaign in Riobamba, specifically in the local newspapers La Prensa and Los Andes, during the period from July to December 2022. To enrich this study, interview techniques were used, involving two journalists, Carlos Chimborazo and Jorge Maciel, both with extensive experience at La Prensa. Most of the publications focus on informative articles, providing objective information about urban tree planting, and are primarily located in short placements. This approach covers various topics related to tree planting and green space management, emphasizing concerns about vandalism and the need to preserve these spaces. Los Andes also opts for informative articles and presents publications in intermediate and short placements. Their headlines suggest a focus on environmental awareness and the quality of the urban environment. Interviews with the journalists revealed significant challenges, such as vandalism and the lack of planning in tree planting projects. They emphasized the crucial role of the media in promoting environmental awareness and the need to involve the community in preserving green spaces.